2021
DOI: 10.1021/acs.jctc.1c00291
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanochemical Tuning of the Porphyrin Singlet-Triplet Gap for Selective Energy Transfer Processes: A Molecular Dynamics Approach

Abstract: Molecular dynamics simulations provide fundamental knowledge on the reaction mechanism of a given simulated molecular process. Nevertheless, other methodologies based on the “static” exploration of potential energy surfaces are usually employed to firmly provide the reaction coordinate directly related to the reaction mechanism, as is the case in intrinsic reaction coordinates for thermally activated reactions. Photoinduced processes in molecular systems can also be studied with these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…S3, ESI † ) have rarely been addressed. Only recently, the importance of such distortions from the planar structure have been shown to be an essential factor for the triplet energy transfer to oxygen: 17 while the porphyrin T 1 vibrational ground state energy is close to the one needed for the excitation of ground state to singlet oxygen, the electron-exchange mechanism is most efficient if this deviation is minimized (resonance condition) by out-of-plane distortions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3, ESI † ) have rarely been addressed. Only recently, the importance of such distortions from the planar structure have been shown to be an essential factor for the triplet energy transfer to oxygen: 17 while the porphyrin T 1 vibrational ground state energy is close to the one needed for the excitation of ground state to singlet oxygen, the electron-exchange mechanism is most efficient if this deviation is minimized (resonance condition) by out-of-plane distortions.…”
Section: Resultsmentioning
confidence: 99%
“…to its first singlet excited state ( 1 D g O 2 ). 17 While there is a general agreement in the literature about this abstract deactivation path, the exact electronic structure of the involved states is debated especially regarding the energetic order of the frontier orbitals in T 1 . 18 Free base 5,10,15,20-tetrakis(4-carboxylatophenyl)porphyrin (TCPP 4À , Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a force can be better applied by a molecular chain of different chemical nature and length, as previously demonstrated by some of the authors. [15,17] As drawback, we should remind that this approach leads unavoidably to an increase of the molecular weight, and therefore the improved E stored has to outbalance the molecular weight increase, in order to finally increase the storage density. In any case, as proof of principle, we show in Figure 6 an example of forceprobes application, including two alkyl chains ((-CH 2 ) 6 -) covalently bound at the ortho positions.…”
Section: Substituent-induced Modification Of the Stored Energymentioning
confidence: 99%
“…Indeed, we have already shown that through mechanochemistry it is possible to modify, in principle, different molecular properties in the electronic ground-state, as well as in the excited-states (e.g., photo-mechanochemistry). [13][14][15][16][17] In the specific of MOST systems, we have recently applied our developed mechanochemistry methodology to the norbornadiene-quadricyclane system but, although storage and activation energies were predicted to be conveniently increased, the norbornadiene absorption energy could only be negligibly red-shifted. [12] Molecular solar-thermal systems (MOST) have emerged in these last years as a novel concept to store solar light.…”
mentioning
confidence: 99%